Application of Integrated Mine Automation System in Zhaogu No.1 Coal Mine - QIAO Bei-bei; JIANG Jun; MIAO Jin-kuang; ZHANG Wen-ke (Gong-kuang zidonghua, 2011)
The paper introduced network structure of whole mine integrated automation system based on industrial Ethernet ring network and its application in Zhaogu No.1 Coal Mine, and analyzed problems in its application. The actual application showed that the establishment of integrated automation system greatly improves production automation and modernized management level of Zhaogu No.1 Coal Mine and realizes remote monitoring, unified management and data share of real-time data and running state of whole mine system.